SPIRITUALITAS, TRANSENDENSI FAKTISITAS, DAN INTEGRASI SOSIAL - Heriyanto, Husain (Khazanah: Jurnal Studi Islam dan Humaniora, 2018)
Abstract: This article is aimed to provide an epistemological framework to arrange the account for the importance and relevance of Islamic spirituality along with its Sufism tradition in relation to keep social integration in contemporary global society particularly in Indonesia.  One of the reasons of this effort is driven by a fact that the rising influence of extrimism among young Muslim generation as well as students has led the growing emergence of social disintegration forces in Muslim communities and countries. Another concern of this article is the decline of knowledge related to the Islamic intellectual and spiritual tradition among Muslim academicians. Due to intellectual capitulation of liberal modernist Muslim scholars on one side and shallow interpretation of Muslim puritanical fundamentalism on the other side, many Muslim people have been in a complete break with traditional Islamic teachings including Sufism. The core thesis of this article is that Sufism as well as Islamic intellectual tradion in general can be elaborated in a such profound way that it has tremendous capacity to provide Muslim society with vision and insight for recovering and flourishing social integration.  Its rationale is that the best way to integrate human society is first of all to integrate oneself. Abstrak: Artikel ini bertujuan untuk memberikan kerangka kerja epistemologis yang akan menjabarkan pentingnya dan relevansi spiritualitas Islam bersama dengan tradisi tasawufnya dalam kaitannya untuk menjaga integrasi sosial dalam masyarakat global kontemporer khususnya di Indonesia. Signifikansi  penjabaran ini karena adanya fakta meningkatnya pengaruh ekstrimisme di kalangan generasi muda Muslim dan juga mahasiswa yang telah menyebabkan meningkatnya kekuatan disintegrasi sosial di komunitas dan negara Muslim. Fokus lain dari artikel ini adalah berkurangnya kajian-kajian terkait dengan tradisi intelektual dan spiritualitas Islam di kalangan akademisi Muslim. Karena kapitulasi intelektual para sarjana Muslim modernis liberal di satu sisi dan di sisi lain kedangkalan interpretasi dari fundamentalisme Muslim puritan, banyak kaum Muslim mengalami kesenjangan dengan ajaran Islam tradisional, termasuk tasawuf. Tesis inti dari artikel ini adalah bahwa tasawuf dan tradisi intelektual keislaman dapat dielaborasi secara mendalam sehingga dapat memberikan pandangan maupun pencerahan yang dapat memulihkan dan menumbuhkembangkan integrasi sosial kepada masyarakat Muslim. Dasar pemikirannya adalah bahwa cara terbaik untuk mengintegrasikan masyarakat manusia adalah dimulai dengan mengintegrasikan diri sendiri.